Press coverage of obesity in Spanish on-line newspapers: treatment and specialization according to the sections - Gurrutxaga-Rekondo, Guillermo (2024)
Obesity is a problem with increasing affection in societies such as Spain, where projections point to the existence of 26 million people affected by the year 2030. This research analyzes the degree of specialization that the Spanish on line media show when addressing this problem in your information. To do this, we have resorted, on the one hand, to content analysis and, on the other, to the theory of agenda setting. The news published by the on line editions of ABC, El País, La Vanguardia and El Mundo, as well as by El Confidencial and El Diario in which some mention is made (n=2.760) have been analyzed as well as those in which it is addressed as the main theme. The results show a growing appearance of the subject in the Spanish media. However, on most occasions when they mention it, they do not do so to address it as the health problem it represents, which would entail the regular inclusion of these news in specific sections directly linked to health or science. On the contrary, information in which some allusion is made to obesity is included in very different sections. At the same time, and in connection with the previous conclusion, there are few journalistic pieces that address childhood obesity, to which the WHO has paid special attention. Hence it can be concluded that the media address obesity with little journalistic specialization.